Ultrafast and surfactant-free synthesis of Sub-3 nm nanoalloys by shear-assisted liquid-metal reduction. Issue 10 (14th September 2020) - Zhang, Mengjie; Zhu, Wenchang; Yang, Xingzhe; Chen, Hao; Feng, Hongbin
Abstract : A general route for synthesizing sub-3 nm nanoalloys on a carbon support via a shear-assisted liquid-metal reduction strategy is reported. Abstract : The uniform and surfactant-free synthesis of ultrafine alloy nanoparticles (NPs) still remains an ongoing challenge. Here, we developed a general route for synthesizing sub-3 nm nanoalloys on a carbon support via a shear-assisted liquid-metal reduction (SA-LMR) strategy. The utilization of shearing treatment resulted in the rapid release of electrons from the liquid sodium-potassium (NaK) alloy, which enabled the ultrafast reduction of precursor metal ions to metallic nanoalloys at room temperature. As a model system, Pt–Cu NPs with uniform distribution were synthesized and characterized by spectroscopic and microscopic techniques. The size, composition and structure of the Pt–Cu NPs could be tuned by controlling the volume of liquid NaK alloy and the reaction time. To prove the universality and utility of our method, the binary Pt–M (Fe, Co, Ni, and Cu) and ternary Pt–Cu–Fe nanoalloys deposited on a carbon support were prepared as hydrogen evolution reaction (HER) catalysts. This facile, rapid and universal synthesis technique has the potential to be employed in the large-scale production of nanomaterials and suggests a new direction for nanoalloys.